Chairil Anwar STUDI KORELASI ANTARA VARIAN PRODUK TERHADAP MINAT PENGUNJUNG EDU MINA WISATA UNTUK PENINGKATKAN PENDAPATAN PADA POLITEKNIK KELAUTAN DAN PERIKANAN SIDOARJO: Program Studi Akuntansi, Universitas Nahdlatul Ulama Sidoarjo *e-mail: chairil_anwar@unusida.ac.id - Chairil Anwar (GREENOMIKA, 2019)
Visitors interest edu mina tour Polytechnic of Marine and Fishery Sidoarjo influenced by Tourism Product Variant that is product of fishery product, fishery product tourism product, fishery tourism service product). The availability of fish culture process as part of cultivation education, including the processed fish, also the completeness of the main object of tourism and its prasarananya as well as services of tourism managers and tourism environment including the surrounding community will lead to increased interest of visitors edu mina wisata. To know the correlation of product variant of tourism to visitor interest of edu mina wisata, need empirical verification. The study population of 569 people spread over 3 groups. The sampling of 254 people was done by random sampling technique (tabulation of Isac and Michae). Two variables in the research are: variant of tourism product and visitor interest of edu mina wisata taken through questionnaire.Data quality test using One Sampel Kolmogorov- Smirnov Test (Minitab 14), Instrument Quality Test using SPSS 16, and Reliability test with Alpha formula. Classic assumption test using Durbin-Watson Aotukorelasitas Test, Multikolineritas Test with VIF (Varian Infalaction Factor) <5 & R2 high, Heteroscedasticity test with scater plot, P-value Normality> 0,05 Test Regression Model through F Test and T test , and interpretation of output model MINITAB 14. Multiple linear regression result there is positive influence of variant of tourism product variables (0,384) and tourism product variant (0,455) to visitor interest of tourism edu mina 84,4% and the rest equal to 15,6% explained by another factor. There is a positive influence of product variant on the interest of visitors of edu mina wisata together or partially.